Determinants of Capital Structure: A Case of Listed Energy Sector Companies in Pakistan - Ghani, Kashif; Bukhari, Syed Husnain (JISR management and social sciences & economics, 2010)
This study is aimed at determining the capital structure of listed energy sector companies in Pakistan, with a view to finding out the impact of four variables, i.e. tangibility, size, growth and profitability of the firms on their leverage. The sample included data for 20 companies for the period spanning 2004 to 2008. Our results show that all these factors affect the leverage of a firm in some degree. We found that tangibility and size have positive association with leverage which supports the predictions of Static Tradeoff Theory. On the other hand, profitability was found to have negative relationship with a firm‟s level of debt, a finding that supports the viewpoint presented by Pecking Order Theory. Growth had positive relationship with leverage thus supporting the simple version of Pecking Order Theory.